Modulating Salmonella Typhimurium's Response to a Changing Environment through Bacterial Enhancer-Binding Proteins and the RpoN Regulon - Hartman, Christine E.; Samuels, David J.; Karls, Anna C. (Frontiers in Molecular Biosciences, 2016)
Transcription sigma factors direct the selective binding of RNA polymerase holoenzyme (Eσ) to specific promoters. Two families of sigma factors determine promoter specificity, the σ70 (RpoD) family and the σ54 (RpoN) family. In transcription controlled by σ54, the Eσ54-promoter closed complex requires ATP hydrolysis by an associated bacterial enhancer-binding protein (bEBP) for the transition to open complex and transcription initiation. Given the wide host range of Salmonella enterica serovar Typhimurium, it is an excellent model system for investigating the roles of RpoN and its bEBPs in modulating the lifestyle of bacteria. The genome of S. Typhimurium encodes 13 known or predicted bEBPs, each responding to a unique intracellular or extracellular signal. While the regulons of most alternative sigma factors respond to a specific environmental or developmental signal, the RpoN regulon is very diverse, controlling genes for response to nitrogen limitation, nitric oxide stress, availability of alternative carbon sources, phage shock/envelope stress, toxic levels of zinc, nucleic acid damage, and other stressors. This review explores how bEBPs respond to environmental changes encountered by S. Typhimurium during transmission/infection and influence adaptation through control of transcription of different components of the S. Typhimurium RpoN regulon.